Role of Short Stories in Developing English Listening Skill - Jabir, Mohd (Voices of Teachers and Teacher Educators, 2021)
The principal aim of this paper is to highlight the importance of short stories in teaching English listening skills. For this, the investigator adopted qualitative approach to analyse the classroom observations and experiences at the elementary and secondary level in district Kargil (Ladakh). It is found that storytelling or using short stories in language classes are useful for teaching language skills, particularly listening skills, as this technique reduces all the barriers for teaching and learning of the same.